High Stroke Volume Variation Is an Independent Predictor for Decreased Blood Pressure During Hemodialysis. Issue 2 (10th March 2017) - Yoshihara, Fumiki; Kishida, Masatsugu; Ogawa, Koji; Nishigaki, Takayuki; Nakasaki, Hironori; Ishizuka, Azusa; Koezuka, Ryo; Matsuo, Miki; Hayashi, Teruyuki; Nakamura, Satoko
Abstract: It currently remains unclear whether stroke volume variation (SVV) before hemodialysis (HD) is an independent predictor of decreased blood pressure (BP) during HD. Fifty‐two patients were divided into two groups (Decreased BP during HD group: N =  10, Non‐decreased BP group: N =  42). Fractional shortening was lower, and mean arterial pressure (MAP) and SVV were higher in the Decreased BP during HD group. A multiple logistic regression analysis identified low fractional shortening, high MAP, and high SVV as independent predictors of decreased BP during HD. The areas under the ROC curves were as follows: 0.849 for MAP, 0.712 for SVV, and 0.893 for MAP and SVV. Optimal threshold values were 93.0 mm Hg for MAP and 17.3 % for SVV. A multivariate regression analysis identified anemia and a longer dialysis vintage as independently related factors for higher SVV. Our results suggest that high SVV is an independent predictor for decreased BP during HD.